2004
DOI: 10.1002/em.20030
|View full text |Cite
|
Sign up to set email alerts
|

Meat‐related mutagens/carcinogens in the etiology of colorectal cancer

Abstract: Diets containing substantial amounts of red or preserved meats may increase the risk of various cancers, including colorectal cancer. This association may be due to a combination of factors such as the content of fat, protein, iron, and/or meat preparation (e.g., cooking or preserving methods). Red meat may be associated with colorectal cancer by contributing to N-nitroso compound (NOC) exposure. Humans can be exposed to NOCs by exogenous routes (from processed meats in particular) and by endogenous routes. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
328
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 393 publications
(348 citation statements)
references
References 98 publications
6
328
0
4
Order By: Relevance
“…In addition, heme also damages colonic mucosa and stimulates epithelial proliferation in animal models (Sesink et al, 1999). Red meat diet also leads to the formation of hetrocyclic amines and the endogenous formation of N-nitroso compounds (NOCs) (Cross and Sinha, 2004), which are known potent and organ-specific carcinogens (Magee and Barnes, 1956;Preussmann, 1984). Rats that were fed red meat diets showed significantly greater amounts of DNA single-strand breaks, double-strand breaks, and colonic mucous layer thinning than rats that were fed white meat diet (Toden et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heme also damages colonic mucosa and stimulates epithelial proliferation in animal models (Sesink et al, 1999). Red meat diet also leads to the formation of hetrocyclic amines and the endogenous formation of N-nitroso compounds (NOCs) (Cross and Sinha, 2004), which are known potent and organ-specific carcinogens (Magee and Barnes, 1956;Preussmann, 1984). Rats that were fed red meat diets showed significantly greater amounts of DNA single-strand breaks, double-strand breaks, and colonic mucous layer thinning than rats that were fed white meat diet (Toden et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, both types of compounds have been shown to be carcinogenic through the induction of mutations (de Kok and van Maanen, 2000;Goldman and Shields, 2003;Cross and Sinha, 2004).…”
Section: Polycyclic Aromatic Hydrocarbons and Heterocyclic Aminesmentioning
confidence: 99%
“…In case meat is grilled over a direct flame, fat/meat juices often drip onto the hot fire, yielding flames containing a number of PAHs which can adhere to the surface of the food. However, PAHs can also be produced during the curing and the processing of the food, for example, when smoking is used as a preservation method (Phillips, 1999;Cross and Sinha, 2004 (IARC, 2013). PAHs are not genotoxic as such, but are activated through metabolization.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
See 2 more Smart Citations